2009
DOI: 10.1016/j.homp.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of basophil activation by histamine: a sensitive and reproducible model for the study of the biological activity of high dilutions

Abstract: Successively, using different models to study of human and murine basophil activation, we demonstrated that high dilutions of histamine, in the range of 15-17CH induce a reproducible biological effect. This phenomenon has been confirmed by a multi-center study using the HBDT model and by at least three independent laboratories by flow cytometry. The specificity of the observed effect was confirmed, versus the water controls at the same dilution level by the absence of biological activity of inactive compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Indeed, some groups and commercial kits use EDTA as an anti-coagulant and add calcium/magnesium to enable the stimulus-dependent induction of a CD63 hi basophil population. 58,59 However, adding exogenous calcium/magnesium lengthens the procedure and could cause variable results. Moreover, we found that calcium/magnesium affected not only CD63 but also CD203c expression levels, including baseline levels (Fig 3, C and D ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some groups and commercial kits use EDTA as an anti-coagulant and add calcium/magnesium to enable the stimulus-dependent induction of a CD63 hi basophil population. 58,59 However, adding exogenous calcium/magnesium lengthens the procedure and could cause variable results. Moreover, we found that calcium/magnesium affected not only CD63 but also CD203c expression levels, including baseline levels (Fig 3, C and D ).…”
Section: Discussionmentioning
confidence: 99%
“…This line of research clearly demonstrates the biphasic action of a substance: a small dose can exert a stimulatory effect on the recovery and the development of survival capacity of cells that have been previously disturbed by a high dose of the same substance. It is of interest that this stimulatory effect of low dose stress is dependent on the initial exposure condition: the more severe the initial stress conditions, the smaller the 146,172 Bacterial peptides Stimulate adherence Low doses inhibit adherence Leukocytes 173 Podophyllotoxin Cell toxicity Low doses enhance oxidative metabolism Wheat germ 174e176 Arsenite Cell toxicity HDs protect from toxicity Lymphocytes 177,178 Cadmium Cell toxicity HDs protect from cadmium toxicity Neurons 179,180 Glutamate, cycloheximide Neurotoxicity Extremely low doses and HDs protect from neurotoxicity Basophils 14 Histamine Inflammation HDs inhibit basophil activation Basophils 181 Quercetin Inhibit cell activation Low doses enhance formyl-peptide-induced activation concentration required for stimulating survival and hsps induction.…”
Section: Hormesismentioning
confidence: 99%
“…Dilutions such as the 4th and 5th centesimal (4C–5C) dilutions from crude extracts are expected to contain ultra-low concentrations of the purported active ingredient, but still falling within the molecular range since the dilution factor from the first ethanolic extract (mother tincture) is 10 8 –10 10 times. On the other hand, dilutions of 12C (10 24 times) or higher theoretically contain no molecules of the mother tincture since the dilution factor exceeds the Avogadro–Loschmidt limit (Sainte-Laudy and Belon 2009). …”
Section: Introductionmentioning
confidence: 99%